Comparative assessment of the mechanical behaviour of aerated lightweight concrete - Berenguer, Romildo; Mariz, Jairo; Just, Angelo; Monteiro, Eliana; Helene, Paulo; Oliveira, Romilde; Carneiro, Arnaldo (Revista ALCONPAT, 2018)
The present study aims to discuss the effect of air entrainment on the mechanical behavior and durability of molded concrete elements. The experiment was carried out using samples with 4 different masses (1500 kg/m3, 1700 kg/m3, 2000 kg/m3, and 2300 kg/m3) and 3 water/cement ratios (0.63-1:5, 0.50-1:4, 0.43-1:3) that were tested to determine compressive strength, water absorption, void index, and carbonation depth. The results showed significant decreases in performance and in the protection indicators of the armature (water absorption and carbonatation), confirming the need for additional mitigation for the structure (protective paints, stainless steel bars), under penalty of premature loss of durability over its lifetime.